Terapi non bedah pada karsinoma sel basal - Adeline Santoso; I Gusti Ngurah Darmaputra; Dewi Gotama; Sissy Sissy (DiscoverSys Inc., 2021)
Basal cell carcinoma accounts for approximately 75% of non-melanoma skin cancer and 25% of all diagnosed skin cancer in the United States. Epidemiological data show the incidence is increasing significantly by 3% -10% per year worldwide. Changes in life expectancy patterns are associated with an increase in this skin cancer, and the incidence is predicted to increase until 2040. Many factors must be considered in the choice of therapy for a patient, including the patient's general condition, the presence or absence of serious medical problems, the use of antiplatelet or anticoagulant medication. Conservative treatment of asymptomatic and low-risk lesions is recommended, as overly aggressive therapy may have a greater effect than the lesions themselves. Topical therapy and non-surgical therapy are currently quite effective as therapeutic options for low-risk basal cell carcinoma and high-risk basal cell carcinoma. They can be an option in conditions that are contraindicated for surgery. Kasus keganasan karsinoma sel basal (KSB) mencakup sekitar 75% dari kasus kanker kulit non melanoma dan mencakup 25% dari semua kasus kanker yang didiagnosa di Amerika Serikat.Data epidemiologi menunjukkan insiden meningkat signifikan sebanyak 3%-10% per tahun di seluruh dunia. Perubahan pola usia harapan hidup berhubungan dengan peningkatan kanker kulit ini, dan di prediksi insiden akan terus meningkat sampai tahun 2040. Terdapat banyak faktor yang harus dipikirkan dalam pemilihan terapi pada pasien, antara lain keadaan umum pasien, ada atau tidaknya masalah medis serius, penggunaan obat anti platelet atau anti koagulan. Perawatan konservatif pada lesi asimptomatik dan beresiko rendah dianjurkan, dikarenakan terapi yang terlalu agresif mungkin akan memberikan efek yang lebih besar dibandingkan dengan lesi itu sendiri. Saat ini terapi topikal dan terapi non-bedah dikatakan cukup efektif sebagai pilihan terapi untuk KSB resiko rendah dan KSB resiko tinggi serta dapat menjadi pilihan pada kondisi kontraindikasi terhadap tindakan pembedahan.